The relative stability of dislocations embedded in the Beta phase matrix and in martensite phases in copper based alloys - Lovey, Francisco Carlos; Hazarabedian, Alfredo Ernesto; Garcés, J. E. (Comisión Nacional de Energía Atómica; Argentina, 1988)
Fil: Lovey, Francisco Carlos Comisión Nacional de Energía Atómica; Argentina